2021
DOI: 10.1007/s42107-021-00379-8
|View full text |Cite
|
Sign up to set email alerts
|

BIM usage benefits and challenges for site safety application in Indian construction sector

Abstract: Construction industry is highly exposed to accidents than other industries. Due to the multi-disciplinary nature of the construction industry, more than one task is required to be performed at the same time. If safety planning is improper, it may lead to serious accidents on-site, directly affecting overall productivity. Recent technologies such as Building Information Modeling (BIM) have the potential to manage safety on the construction site. This study deals with the status check of the awareness of BIM in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 42 publications
(40 reference statements)
0
12
0
3
Order By: Relevance
“…In the Netherlands, the Government Buildings Agency has mandated the use of BIM for public projects in 2011 [ 2 ]. Research conducted in Germany, France, Brazil and Austria showed that BIM is gaining wide adoption in these countries [ 3 ]. In Estonia, a survey was carried out among 297 firms and revealed that 51 per cent of respondents are already using BIM or planning to adopt it over the next 5 years [ 4 ].…”
Section: Bim Implementation Across the Globementioning
confidence: 99%
“…In the Netherlands, the Government Buildings Agency has mandated the use of BIM for public projects in 2011 [ 2 ]. Research conducted in Germany, France, Brazil and Austria showed that BIM is gaining wide adoption in these countries [ 3 ]. In Estonia, a survey was carried out among 297 firms and revealed that 51 per cent of respondents are already using BIM or planning to adopt it over the next 5 years [ 4 ].…”
Section: Bim Implementation Across the Globementioning
confidence: 99%
“…This indicates that there is a relevance for the knowledge of BIM in the organization to lead the construction industry towards implementing BIM. It will also raise awareness among the construction industry on the benefits of implementation in construction projects (Shalaka Hire et al, 2021;Al-Ashmori et al, 2020;Ullah et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Ahuja et al [12] studied the factors that affect BIM adoption among the Indian architectural firms. Hire et al [13] reported that the absence of knowledge about the advantages of BIM, hesitance to learn the process and change from conventional techniques, absence of a national driver for BIM adoption, variation in BIM readiness among project teams and purchase of software are the significant barriers in the Indian construction industries with the aspect of site safety applications. Kolaric et al [14] analysed the utilization of BIM in the Croatian construction industry and reported that the high cost of software and hardware, lack of consultant's assistance and inadequate BIM knowledge of civil engineers are barriers for the BIM adoption.…”
Section: Introductionmentioning
confidence: 99%